The Academic Profession in Neoliberal Times: A Gendered View - Gaiaschi, Camilla (Professions and Professionalism, 2021)
While witnessing a feminization of its workforce, the academic profession has experienced a process of market-based regulation that has contributed to the precarization of early career phases and introduced a managerial culture based on competition, hyper-productivity, and entrepreneurship. This paper aims to investigate the implications of these changes for female academics. A mixed model research design was used based on administrative data on the Italian academic population and qualitative interviews with life scientists within a specific academic institution. Results show that the implications of university transformations in terms of gender heterogeneity are complex. On the one hand, the increased precarization of early career stages has increased gender inequalities by reducing female access to tenured positions. On the other, the adoption of performance-based practices has mixed consequences for women, entailing both risks and opportunities, including spaces of agency which may even disrupt male-dominated hierarchies.